State of the Art Review of Wearable Devices for Respiratory Monitoring - Zhiyu Jia; Hannah Huth; Wen Qi Teoh; Sheng Xu; Bradford Wood; Zion Tsz Ho Tse (IEEE Access)
Respiratory frequency and volume are essential physiological signals for diagnosing and managing respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD). Wearable devices have emerged as a transformative tool for continuous, non-invasive respiratory monitoring and data portals, providing massive real-time data critical for both clinical and home settings. This state-of-the-art review delves into the advancements and applications of wearable respiratory monitoring devices, specifically focusing on inertial measurement units (IMUs), piezoresistive sensors, and optical fibre sensors. Detailed analyses of sensor designs, sensing methods, and clinical applications are presented, highlighting key studies such as the development of low-cost IMU devices for breathing frequency monitoring and the integration of piezoresistive sensors for real-time respiratory rate detection. This review identifies major challenges, including power efficiency, ergonomic design, data accuracy, and data privacy concerns. It also introduces innovative solutions proposed in recent research. Future research directions are suggested to address these challenges and further enhance the capabilities and reliability of wearable respiratory monitoring devices. This review underscores the potential of wearable technology to improve patient outcomes and reduce resource cost through enabling early diagnosis, facilitating continuous health monitoring, and supporting artificial intelligence applications through data generation.